Lego Serious Play® to Improve Emotional Regulation and Motivation in Nursing Education: A Qualitative Study - Raquel González-Hervías; Leticia López-Pedraza; Marina Gómez de Quero Córdoba; Rosa Raventós-Torner; Roser Cuesta-Martínez; Leyre Rodriguez-Leal (Nursing Education Perspectives, 2026)
The Lego Serious Play® methodology uses LEGO bricks to foster creativity, participation, and meaningful learning. We explored its impact on emotional regulation and motivation in mental health education nursing students. A qualitative study was conducted through reflective writing after group activities (8 to 10 students) involving constructions representing mental health issues, complemented by a Metaplan (participatory, visual methodology using cards to organize and discuss ideas), with symptoms, treatment, and nursing care. Students presented their models, Metaplan, and a podcast on mental health care. Findings revealed perceived advantages and disadvantages of gamification, highlighting its positive influence on motivation and emotional regulation.